KOMPARASI EFEKTIFITAS STRATEGI PEMASARAN DESA WISATA KAMPUNG TERIH BATAM DAN DESA WISATA EKANG ANCULAI BINTAN - Asman Abnur; Mustika, Armen; Amalia, Eva (Puslitabmas Batam Tourism Polytecnic, 2023)
This study aims to compare the marketing strategy managed by two similar tourist destinations in Batam which is KampungTerih and the other one which in Bintan namely Ekang Tourism Village . Kampung Terih and Ekang Tourism Village are tourist destinations that have the concept of a tourism village with beautiful nature and various facilities as well tourist attraction. Both having positive arrival of visits which resulted from the marketing effort to attract visit intetntion. Using qualitative descriptive approach focusing on the marketing development strategies to increase visitor levels are creating new innovations with the products offered so that tourists are more interested and curious and want to visit can go through marketing platform to promoted the attractive tourism packages in describing Kampung Terih and Desa Ekang Anculai but does not eliminate the uniqueness and exclusivity of the village. Following strategis namely product introduction , promotion and repositioning and giving utmost service to visitor or tourist effectively amongst of the best strategies to implement